Pengaruh Silica Fume Pada Pembuatan Beton Polimer - Irene Datuan; Jonie Tanijaya; Desi Sandy (Paulus Civil Engineering Journal, 2023)
Concrete is a construction material composed of aggregate (coarse and fine aggregate), water, cement with or without additives. However, cement production can cause environmental damage such as air pollution. To reduce the use of cement is by using polymers. In the manufacture of polymer concrete, one of the cement substitute materials that can be used is silica fume. This research was conducted based on the Indonesian National Standard (SNI) method and was tested when the concrete had been soaked for 7, 21 and 28 days. This study used a cylinder with a diameter of 15 cm and a height of 30 cm. The results of the concrete test showed that the value (f'c) at 28 days for the 5% silica fume variation was 25.950 MPa and the 10% variation was 23.968 MPa. In testing the split tensile strength of concrete, the value of the split tensile strength of concrete (ft) at 5% silica fume variation is 2.666 MPa and at 10% variation is 2.571 MPa. From the results of the concrete elastic modulus (E) test, the average value of the 5% silica fume variation was 22883.316 MPa and at 10% variation it was 21710.136 MPa. From the test results it can be concluded that the use of silica fume as a substitute for cement can affect the compressive strength, split tensile strength, and modulus of elasticity of concrete.